Avaliação do uso da cinza de casca de arroz residual no tratamento do agregado reciclado de concreto - Nascimento, Aline Cristiane Kumpfer (2023)
The use of recycled concrete aggregates (RCA) in the production of new structures has been investigated in order to minimize the incorrect disposal of construction and demolition waste, and also as a way to reduce the exploitation of aggregates from natural resources. However, the properties of the RCA are inferior to those found in natural aggregates due to the porous and weakened residual mortar present in this material. This condition negatively affects the properties of concrete produced with recycled aggregates. In this context, techniques for removing and/or strengthening the residual mortar have been explored to improve the performance of RCA. One of these techniques is the immersion treatment in pozzolanic mixtures in which materials such as silica fume, metakaolin and fly ashes are used providing a strengthening layer around the aggregate and also filling voids in the residual mortar. In view of this, the present research proposed to investigate the replacement of these commercial materials by residual rice husk ash (RHA). For this, the ash was treated through grinding and reburning, and physically characterized and through isothermal calorimetry tests, pozzolanic activity index and XRD and TG/DTG analysis to choose the ideal grinding time or reburning temperature. It was concluded that the CCA-30, milled for 30 minutes, provided the best mechanical performance in the pozzolanic activity index and was chosen for the treatment of RCA. Subsequently, the RCA were treated in different pozzolanic mixtures of Portland cement and RHA, in proportions 50-50, 70-30, 90-10 and 100% of cement. In addition to the treated samples, a standard sample received no treatment for comparison purposes. After the treatment, the aggregates were physically characterized, and concrete groups were produced to quantify their mechanical properties and the quality of the new ITZ. From the experimental program it was observed that the treatment provided improvement in the properties of the treated aggregates and respective ITZ zones, but without bringing significant improvement to the mechanical properties of the concretes produced with them.